Maritime Independent Villages: A Form of Maritime Resilience Through Strengthening the Capacity of Coastal Communities in Ponipingan Village, Central Sulawesi - TOWADI, Mellisa; PAUWENI, Apriyanto A.J; T. MANDJO, Julius (PT Keberlanjutan Strategis Indonesia, 2024)
This article aims to disseminate service activities in the form of publications related to strengthening village capacity through waste management as a form of maritime resilience of Ponipingan village which is a coastal area of Bunobogu District, Buol Regency. The implementation of activities is carried out using counseling methods about the concept of the integration system